SYNTHESIS AND STUDY OF LUMINESCENT PROPERTIES OF SYSTEM CaSnO3 : Yb3+, RE3+ (RE = Er, Ho, Tm) - Uliana Mar'ina; Aleksandr Mar'in; Viktor Vorob'ev (Вестник Северо-Кавказского федерального университета, 2022)
As an object of a research the luminescent system CaSnO3 : Yb3+, RE3+ where RE3+ - the rare-earth elements Er, Ho, Tm is used. The samples are by a solid-phase method at a temperature of 1 250 °C and duration of calcination of 18 hours synthesized. The X-ray phase analysis confirmed formation of the phase CaSnO3 with the lattice structure characteristic to the «perovskite» type. The spectra of the excitation and luminescence spectra of the samples were analyzed. The luminescence in visible and short-range IK-areas of an electromagnetic range in case of substance excitation by radiation in the range from 260 to 650 nm and the laser with wavelength of960 nm was detected. Dependence of intensity of a luminescence ofsamples on concentration of all activators is set.